Comparative analysis of injection clonidine and injection dexmedetomidine added to injection bupivacaine for spinal anaesthesia in lower abdominal surgeries - Partani, Seema; Chhabra, Alka Kewalramnani; Goyal, Sangeeta; Sharma, Nagendra Prasad; Bhateja, Saurabh; Gupta, Shashank (International Journal of Research in Medical Sciences, 2017)
Background:Efficacy of sub-arachnoid block can be improved by addition of various adjuvants to local anesthetics. Intrathecal administration of clonidine or dexmedetomidine has improved the quality of spinal anesthesia in terms of longer duration of post-operative analgesia with comparatively lesser side effects. In present study we compared the onset and duration of motor and sensory block, hemodynamic effects, post-operative analgesia and adverse effects of clonidine and dexmedetomidine used intrathecally with bupivacaine. Methods: Present study was conducted in 150 patients (ASA class I and II) undergoing lower abdominal surgeries. Patients were randomly divided into three group’s viz. B, C and D. Group B received bupivacaine (12.5 mg), group C received clonidine (30 µg) with bupivacaine and group D received dexmedetomidine (5 µg) with bupivacaine. Volume of administered drug was set at 3ml in all the groups. The onset time to reach peak sensory and motor block level, regression time to sensory and motor block, hemodynamic changes and side effects if any were assessed and recorded. Results: In our study we observed that there was no significant difference in patient demography and duration of surgical procedure. The time to onset of sensory blockage was similar in all the three groups but time to onset of motor block was shorter in group C and D compared to group B. Total duration of sensory and motor block was significantly higher in group D compared to group C and B. The duration of sensory block in group D was 139.58+14.49, in group C it was 122.46+18.55 and in group B it was 100+13.43 minutes. The duration of motor block in group D was 250.40+27.33, in group C it was 229.28+23.68 and in group B it was 175.64+17.41 minutes. Conclusions: It was concluded that though both clonidine and dexmedetomidine prolonged duration of sensory and motor block of Bupivacaine, Dexmedetomidine is better in terms of longer duration of action.